2012
DOI: 10.5194/cp-8-1067-2012
|View full text |Cite
|
Sign up to set email alerts
|

A 500 kyr record of global sea-level oscillations in the Gulf of Lion, Mediterranean Sea: new insights into MIS 3 sea-level variability

Abstract: Abstract. Borehole PRGL1-4 drilled in the upper slope of the Gulf of Lion provides an exceptional record to investigate the impact of late Pleistocene orbitally-driven glacioeustatic sea-level oscillations on the sedimentary outbuilding of a river fed continental margin. High-resolution grainsize and geochemical records supported by oxygen isotope chronostratigraphy allow reinterpreting the last 500 ka upper slope seismostratigraphy of the Gulf of Lion. Five main sequences, stacked during the sea-level lowerin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 59 publications
0
27
0
4
Order By: Relevance
“…For the last ca. 500 kyr, borehole data demonstrated that shelf deposits are primarily made up of forced-regressed sequences formed in response to 100 kyr glacio-eustatic cycles (Bassetti et al, 2008;Frigola et al, 2012;Sierro et al, 2009). These authors also demonstrated that higher frequency cycles, as well as suborbital climate changes, were nicely recorded within paleo-prodeltaic sedimentary archives.…”
Section: Geological Evolution Of the Rhône Subaqueous Deltamentioning
confidence: 99%
“…For the last ca. 500 kyr, borehole data demonstrated that shelf deposits are primarily made up of forced-regressed sequences formed in response to 100 kyr glacio-eustatic cycles (Bassetti et al, 2008;Frigola et al, 2012;Sierro et al, 2009). These authors also demonstrated that higher frequency cycles, as well as suborbital climate changes, were nicely recorded within paleo-prodeltaic sedimentary archives.…”
Section: Geological Evolution Of the Rhône Subaqueous Deltamentioning
confidence: 99%
“…Entre 100 y 530 ka el modelo de edad se obtuvo por sincronización del registro de δ 18 O del sondeo PRGL1-4 con el registro de isótopos bentónicos LR04 (Lisiecki y Raymo, 2005) (Frigola et al, 2012). La resolución temporal derivada del modelo de edad oscila entre los 160 y los 1550 años durante los períodos glaciales y los interglaciales, respectivamente.…”
Section: Figura 1 Mapa Batimétrico Del Golfo Del León (Modificado Deunclassified
“…Esta observación, junto con la cronoestratigrafía basada en el registro de δ 18 O de G. bulloides (Sierro et al, 2009) (Fig. 2D), revela que cada una de estas unidades corresponde a un episodio regresivo de bajada del nivel del mar durante un ciclo interglacial/glacial de 100 ka (Frigola et al, 2012). Se ha podido interpretar así el modelo deposicional del talud superior del GoL, donde se han identificado siete unidades (S1, S2a, S2b, S3a, S3b, S4 y S5) (Jouet, 2007) (Fig.…”
Section: En El Perfil Se Ilustran Las Secuencias Sismoestratigráficasunclassified
See 2 more Smart Citations